Peningkatan Pertumbuhan Suplir dengan Pupuk Kompos Organik di Kelompok PKK RT 20, Pakuan Baru, Jambi - Nasution, Hasriati; Suryanto; Emanauli (Studium: Jurnal Pengabdian Kepada Masyarakat, 2024)
Adiantum, commonly known as Maidenhair Fern, holds significant popularity as an indoor and outdoor ornamental plant due to its air-purifying capabilities and health benefits. Optimal growth of this plant necessitates fertile soil conditions, achievable through the use of enriched organic compost fertilizers. This study aims to enhance the understanding and application of enriched organic compost fertilizers among the women of PKK RT 20 in Pakuan Baru District, Jambi City, for the cultivation of Maidenhair Fern. Through a series of workshops and practical demonstrations, the women were provided with the necessary knowledge and skills to effectively manage enriched organic compost fertilizers. The outcomes of this approach are expected to elevate awareness and implementation of enriched organic compost fertilizer usage in Maidenhair Fern cultivation, thereby yielding optimal plant growth and aesthetic satisfaction.